Resident Perceptions of New Urban Tourism: A Neglected Geography of Prejudice. Issue 5 (May 2015) - Dirksmeier, Peter; Helbrecht, Ilse
Abstract Research on urban tourism has focused on the search for alternative, authentic, lively, and mundane urban neighbourhoods by visitors. This so‐called new urban tourism is characterised by the increasing quest by tourists for contact with mundane life in ordinary residential quarters. The intrusion of new urban tourism into day‐to‐day life also affects residents' perceptions of visitors, which are prone to become stereotypes and prejudices rather than just perceptions. The paper offers a review of the urban residents' perceptions research literature through the lens of the new urban tourism phenomenon, aligning it with wider geographies of prejudices. Consequently, the paper argues that an understanding of residents' attitudes towards the new urban tourism phenomenon offers a framework through which geographies of prejudices subtly at work in these resident/visitors encounters can be more deeply researched.